On Lattice Distortion in High Entropy Alloys - He, Quanfeng; Yang, Yong (Frontiers in Materials, 2018)
Lattice distortion in high entropy alloys (HEAs) is an issue of fundamental importance but yet to be fully understood. In this article, we first focus on the recent research dedicated to lattice distortion in HEAs with an emphasis on the basic understanding derived from theoretical modeling and atomistic simulations. After that, we discuss the implications of the recent research findings on lattice distortion, which can be related to the phase transformation, dislocation dynamics and yielding in HEAs.